Optimizing Organizational Performance: A Human Resource Management Approach in Higher Education - Khuzaini, Khuzaini; Irpan, M; Shaddiq, Syahrial (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This paper aims to analyze organizational performance optimization through human resource management at one of the tertiary institutions in Banjarmasin. This study uses a descriptive qualitative approach. Data were obtained from the results of interviews, observation, and documentation. The data analysis was carried out in stages, starting with data reduction, data presentation, and conclusion. The study results show that optimizing organizational performance through human resource management at UNISKA Banjarmasin is carried out using; a focus on achieving vision and mission targets, competitive recruitment and selection policies, employee career development, sustainable performance appraisal policies, monitoring, and evaluation. This research has implications that there are various challenges in implementing human resource management in tertiary institutions, such as limited human resources, differences in culture and values, and difficulties in flexibility. Therefore, several solutions are needed to deal with these problems, such as using technology and automation, increasing awareness of values and culture, and developing employee engagement programs.